Conflict Management and Resolution at SMKN 1 (the State Vocational School 1) Depok, West Java, Indonesia - Lusi Triana; Dadan Zulkifli (Arus Jurnal Psikologi dan Pendidikan, 2022)
Conflict can undermine the achievement of the necessary goals if it occurs in an organization then its impact can be minimized by properly monitoring the struggle. The purpose of this study is to describe the conflict in an organization, especially at SMKN 1 Depok about what variables can cause conflict, how to approach the conflict, and the impact of organizational implementation of the conflict. The research was conducted using a literature study. Identification of the authenticity and quality of literature is carried out by researchers by searching and compiling reference lists with software such as Google Scholar, and the Mendeley desktop (citation and reference manager). The study findings reveal that (1) there are three possible interpretations of the conflict, namely positive, neutral, and negative meanings, and (2) both internal and external elements within a particular organization can be a source of the conflict. Internal impacts include things like personality differences, stress, and decreased productivity, while external influences include things like inadequate communication, lack of resources, sexual harassment, etc., (3) and conflict resolution strategies require leadership skills. There are eight methods for resolving disputes: deliberation, third-party intervention, confrontation, negotiation, compromise, mediation, conciliation and consultation, and resource allocation, and (4) conflict can interfere with one's performance, but not all disputes are bad; if managed well, disagreements can even be beneficial.